Macro-Hedging for Commodity Exporters - Borensztein, Eduardo; Jeanne, Olivier; Sandri, Damiano (Washington, D.C. : International Monetary Fund, 2009)
This paper uses a dynamic optimization model to estimate the welfare gains of hedging against commodity price risk for commodity-exporting countries. The introduction of hedging instruments such as futures and options enhances domestic welfare through two channels. First, by reducing export income volatility and allowing for a smoother consumption path. Second, by reducing the country's need to hold foreign assets as precautionary savings (or by improving the country's ability to borrow against future export income). Under plausibly calibrated parameters, the second channel may lead to much larger welfare gains, amounting to several percentage points of annual consumption.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet